The influence of percussion massage on knee's range of motion in two positions - Klimowska Natalia; Jaskulski Karol; Zdrodowska Agnieszka (Sciendo, 2023)
Study aim: The practical application of vibration stimuli is increasingly observed in physiotherapy and sports. The aim of the study was to investigate the effects of local vibration on knee-joint range of motion (ROM) improvement among male American football players.